2020
DOI: 10.3390/ijerph17196964
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Assessment of COVID-19 Symptoms: Gender Differences and Communication Routes for the Generation Z Cohort

Abstract: This paper explores the generation Z (Gen Z) cohort’s self-assessed knowledge regarding the coronavirus disease 2019 (COVID-19) symptoms as well as their interest in acquiring information and learning more about the transmission and spread of the severe acute respiratory syndrome coronavirus 2 (SARS-COV-2 virus) and the COVID-19 symptoms. Additionally, it investigates gender differences in self-assessed knowledge of COVID-19 symptoms. Field research employing a nonprobability sampling method with an online que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 67 publications
4
8
0
1
Order By: Relevance
“…We observed that women in our sample were more likely to report positive attitudes toward using an app or website to track potential COVID-19 exposures or symptoms compared to men. This is consistent with prior studies that focused on disparities in mHealth use among the general population [ 80 , 89 ]. Previous studies have also documented lower rates of using mHealth tools among individuals with lower socioeconomic backgrounds compared to individuals with higher socioeconomic backgrounds [ 81 , 90 ].…”
Section: Discussionsupporting
confidence: 92%
“…We observed that women in our sample were more likely to report positive attitudes toward using an app or website to track potential COVID-19 exposures or symptoms compared to men. This is consistent with prior studies that focused on disparities in mHealth use among the general population [ 80 , 89 ]. Previous studies have also documented lower rates of using mHealth tools among individuals with lower socioeconomic backgrounds compared to individuals with higher socioeconomic backgrounds [ 81 , 90 ].…”
Section: Discussionsupporting
confidence: 92%
“…Thus, previous research does not provide clear clues to understand Generation Z acceptance of service robots as hospitality customers, neither in general nor for the current pandemic. Similarly, preventive health-care literature about Generation Z members and COVID-19 does not consider robotization or other technologies either, focusing on what media are appropriate for conveying information about the disease to this generational cohort (Kamenidou et al, 2020). Thus, we conduct our literature review without circumscribing it to any generational cohort or age group.…”
Section: Introductionmentioning
confidence: 99%
“…In response to manage the COVID-19 pandemic effectively, the Malaysian government implemented several legislative interventions, including the imposition of different MCO levels, active case detection and provision of educational resources concerning COVID-19. Although numerous studies were conducted across the globe (11)(12)(13)(14), and few conducted locally (15), to provide information on KAP to reveal the knowledge gaps and to advise the relevant authorities for targeted strategies, the findings of their study might not be applicable to the local setting, given the (i) non-pharmacological interventions implemented differently, compared to other countries (16), and (ii) the scarcity of reliable tool developed and validated in Malay (national language in Malaysia). Information on communication routes affected the awareness and knowledge of COVID-19 (14); hence, the health literacy component is recommended to be evaluated along with the KAP assessment.…”
Section: Challenges In the Assessment Of Kaphmentioning
confidence: 99%